The influence of topic and systemic administration of copaiba oil on the alveolar wound healing after tooth extraction in rats - Dias-da-Silva, Marco-Antonio; Pereira, Andresa-Costa; Marin, Miguel-Christian-Castillo; Salgado, Miguel-Angel-Castillo [UNESP] (Medicina Oral, S.L., 2013)
The Copaiba oil has been used as an auxiliary treatment of inflammations, skin disorders and stomach ulcers, however, in dentistry, this alternative medicine has not been investigated yet. The purpose of this study was to evaluate the influence of topic and systemic administration of copaiba oil on the alveolar wound healing after tooth extraction. Twenty-eight wistar male rats had their lower first molar teeth extracted. Subsequently, they were divided in four groups, according to the treatment performed: (a) alveolar socket irrigation with copaiba oil; (b) alveolar socket irrigation with physiological serum; (c) daily gavage with copaiba oil or (d) daily gavage with physiological serum. After the sacrifice, the mandibles were removed and processed in order to obtain decalcified histological sections. The results demonstrated high level of epithelial migration, small number of inflammatory cells and vascular enhancement in the animals which received systemic administration of copaiba oil. The rats treated with topic administration of copaiba oil presented ulcerations and large number of inflammatory cells. An increased bone neoformation was observed in both groups treated with copaiba oil when compared with placebo group. It could be concluded that topic or systemic administration of copaiba oil leads to a better alveolar bone healing, however the topic application on connective tissue should be carefully considered, regarding the whole socket wound healing. © Medicina Oral S. L. C.I.F. B 96689336 - eISSN: 1989-5488.
Keywords: Alveolar wound healing; Copaiba; Oil-resin